2021
DOI: 10.48550/arxiv.2105.15180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sound emission and annihilations in a programmable quantum vortex collider

W. J. Kwon,
G. Del Pace,
K. Xhani
et al.

Abstract: In quantum fluids, the quantisation of circulation forbids the diffusion of a vortex swirling flow seen in classical viscous fluids. Yet, a quantum vortex accelerating in a superfluid may lose its energy into acoustic radiation 1,2 , in a similar way an electric charge decelerates upon emitting photons. The dissipation of vortex energy underlies central problems in quantum hydrodynamics 3 , such as the decay of quantum turbulence, highly relevant to systems as varied as neutron stars, superfluid helium and ato… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…In contrast, the KG vortex dipole will move along the dipole axis and annihilate each other, due to the absence of a velocity field. Related observations of vortex dynamics were reported in [44]. We note that the particle-hole symmetry is the origin of this qualitatively distinct behaviour from GP fluid dynamics.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, the KG vortex dipole will move along the dipole axis and annihilate each other, due to the absence of a velocity field. Related observations of vortex dynamics were reported in [44]. We note that the particle-hole symmetry is the origin of this qualitatively distinct behaviour from GP fluid dynamics.…”
supporting
confidence: 82%
“…Our work reveals that turbulence in a BCS superconductor and its scaling laws might deviate from Kolmogorow scaling laws [46], which apply to classical systems as well to GP fluids. We note that our predictions could be experimentally confirmed using refined experimental technique, such as in situ observations of two dimensional Fermi liquids when probing the BEC-BCS crossover in neutral atoms [47,48] or the well controlled imprinting of vortex dipole pairs [44].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…[22][23][24][25][26]. Laser stirring is also employed to generate controlled vortex distributions [27][28][29]. A number of theoretical studies was reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly relevant for studies of quantum turbulence where one might want to reproducibly generate a many-vortex state to look for signatures of quantum turbulence in subsequent vortex dynamics. Progress towards a flexible experimental vortex architecture has been made in highly-oblate singlecomponent BECs regarding deterministic placement of individual vortex cores [25], with subsequent refinement made possible by the development of arbitrary configurable optical potentials [26,27]. However, a fully flexible architecture would benefit from the further development of additional experimental techniques that allow for controlled placement of a cluster of a fixed number of vortices, all with the same sign of circulation.…”
Section: Introductionmentioning
confidence: 99%